Overview of the Implementation of Health Promotion Programs for Diabetes Mellitus Patients in Hospital - Diana Dewi Hestia; Mahendro Prasetyo Kusumo (Rifa'Institute, 2022)
Introduction: Health promotion is an effort to create people to improve and maintain their health. Improper implementation of Health Promoting Hospital (HPH) can increase recurrence and mortality rates, decrease patient satisfaction, and increase patient care costs in hospitals. Various epidemiological studies show a tendency to increase the incidence and prevalence of Type 2 Diabetes Mellitus in various parts of the world. The WHO organization predicts a large increase in the number of Type 2 Diabetes Mellitus patients in the coming years. Objective: This study aims to describe the implementation of health promotion programs in Type 2 Diabetes Mellitus patients in the hospitals. Method: The type of this research is a descriptive analysis with a quantitative approach. The population in this study were outpatients for Type 2 Diabetes Mellitus at the Internal Medicine Polyclinic in Panembahan Senopati Bantul Hospital and PKU Muhammadiyah Yogyakarta Hospital. The sampling technique used is quota sampling, the number of sample used is 440 patients. The instrument used is a questionnaire. Data analysis in this study used categorical description analysis. Result and Discussion: The results showed that 83.3% (out of 233 DM patients at Panembahan Senopati Hospital Bantul) and 64.3% (out of 207 DM patients at PKU Hospital Yogyakarta City) stated that health promotion at the hospital was good. The results of the study on patient assessment standards and patient information and intervention standards also showed good results. Conclusion: So it can be concluded that health promotion in Panembahan Senopati Bantul Hospital and PKU Muhammadiyah Yogyakarta Hospital in general is good